14+5x=3(-3x+3)-11

Simple and best practice solution for 14+5x=3(-3x+3)-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14+5x=3(-3x+3)-11 equation:


Simplifying
14 + 5x = 3(-3x + 3) + -11

Reorder the terms:
14 + 5x = 3(3 + -3x) + -11
14 + 5x = (3 * 3 + -3x * 3) + -11
14 + 5x = (9 + -9x) + -11

Reorder the terms:
14 + 5x = 9 + -11 + -9x

Combine like terms: 9 + -11 = -2
14 + 5x = -2 + -9x

Solving
14 + 5x = -2 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
14 + 5x + 9x = -2 + -9x + 9x

Combine like terms: 5x + 9x = 14x
14 + 14x = -2 + -9x + 9x

Combine like terms: -9x + 9x = 0
14 + 14x = -2 + 0
14 + 14x = -2

Add '-14' to each side of the equation.
14 + -14 + 14x = -2 + -14

Combine like terms: 14 + -14 = 0
0 + 14x = -2 + -14
14x = -2 + -14

Combine like terms: -2 + -14 = -16
14x = -16

Divide each side by '14'.
x = -1.142857143

Simplifying
x = -1.142857143

See similar equations:

| 7k+5=4k-19 | | 6n-8=16 | | 2k-4=(-8) | | 3Z+6=15 | | m^2-16m-11=0 | | -8u+6(u+6)=20 | | 6s+34=6+4(2s+4) | | x^2-6x+104=4 | | 256=8(4x+12) | | z+13.53=2.53 | | z-2.53=13.53 | | .47z=5.17 | | 8.25y=-82.5 | | 7x+5y=-9 | | y*-5=-.02 | | 32+7x=x+8(4+6x) | | .75y=-7.5 | | x+5+4x-55+7x-130=180 | | -29=-3x-4(-x+10) | | 16.93+y=26.93 | | 17+m=20 | | m-2=1 | | 8x+5+4x-5+11x+10=180 | | 2(x-3)+5=4y-3(x+y) | | log(x)200=15 | | -4y^2-11y-8= | | -9m=27 | | 3(-(5u+1)-(-4u+3))=5(u+4) | | 4(-7x+13)=-144 | | s^2-4s-10=0 | | 4(-7+13)=-144 | | 5v-4=-14 |

Equations solver categories